(3SQ GdSGdcjf hSQGL GdSGFQjfs
(3ChdgG (B:s
(3GdMeO ddg GdPi Cf aj GdCRd ChdkG ehLhOkGHhLhOg s
(3BNQgG (B:s
(3TaGA Gddg ef OGA GdZjhH ZaQ Gddg dg hdhGdOjg hdLejY GdeDefjf hGdeDefGJ hGdeSdejf hGdeSdeGJ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJUha hGdBOGH GdTQYjIs